The value of CEOs' supply chain experience: Evidence from mergers and acquisitions - Fich, Eliezer M.; Nguyen, Tu (Journal of Corporate Finance, 2020)
Acquirer CEOs with experience in the target's industry supply chain (‘supply chain CEOs’) are associated with wealth effects of first-order importance: they earn 1.5% higher merger announcement returns. Conversely, their targets get a lower share of the merger gains. Acquisitions by supply chain CEOs also exhibit higher synergies, better post-deal accounting performance, and less goodwill written off. These findings withstand checks for endogeneity, anticipation bias, and numerous robustness tests. In takeovers by supply chain CEOs, superior acquirer performance stems from both value creation and rents negotiated away from target shareholders.